Business managers’ knowledge and leadership behaviour in relation to artificial intelligence in Nelson Mandela Bay - Fourie, Tiaan Jakobus (The IIE, 2019)
South Africa is in an interesting situation, whereby the country needs to make an important decision; does the country embrace, manage and assist in developing the Fourth Industrial Revolution (Industry 4.0). Artificial intelligence (AI) is a key driver of Industry 4.0, and invaluable for knowledge management in terms of data storage, management and dissemination. The processes required for AI development and its’ embracement is largely dependent on leadership behaviour in South Africa and the world. This study has focussed on the leadership behaviour and knowledge of business managers in Nelson Mandela Bay (NMB) with regards to AI, and how AI is able to assist knowledge management within organisations. This research report implemented a combination of purposive, convenience and snowball sampling, due to specific constraints. The data was collected and interpreted from 25 business managers, utilising descriptive statistics. AI is the main concept of evaluation when Industry 4.0 is discussed. This research report has indicated that the sample of business managers would trust AI in certain circumstances, however, their leadership behaviour towards AI is sceptical, and they have a knowledge gap. The research also indicated that employees do have opportunities to develop their skills.
Keywords: leadership behaviour; business manager; Artificial Intelligence; Industry 4.0; knowledge management; Service Industry